Motivational Interviewing (MI) in Obesity Care: Cultivating Person‐Centered and Supportive Clinical Conversations to Reduce Stigma: A Narrative Review - Violeta Moizé; Yitka Graham; Ximena Ramos Salas; Mercè Balcells (Obesity Science & Practice)
ABSTRACT Background Patients perceive high levels of weight prejudice, stigma, and discrimination within health systems, affecting their ability to manage their obesity and related chronic conditions. Scientific and patient obesity associations worldwide have prioritized the reduction of weight stigma to improve patient experiences in health systems and overall health outcomes. Since a significant proportion of the population is now living with multiple chronic diseases related to obesity, healthcare systems must shift toward multi‐disease management frameworks incorporating person‐centered and non‐stigmatizing clinical conversations. Motivational Interviewing (MI) has the potential to transform clinical interactions by using non‐stigmatizing language, communication, and practices. Studies using MI in obesity management have solely focused on weight loss outcomes, while other patient experience related outcomes would also be relevant to evaluate. Methods A narrative review was undertaken to critically analyze the potential impact of MI on obesity and chronic disease management practices and experiences. Findings An analysis and contextualization of the MI theoretical framework for obesity management, based on the philosophy of motivational spirit, was reviewed, assessing micro skills or strategies. Conclusion MI may assist healthcare professionals conduct non‐stigmatizing clinical conversations in accordance with basic principles of collaborative therapeutic alliances. A proposal for research considerations that can help illuminate the potential for of MI in obesity management is also outlined.